A Thousand Contradictory Ways: Addiction, Neuroscience, and Expert Autobiography - Fraser, Suzanne (2015)
Neuroscientific accounts of addiction are increasingly influential in health and medical circles. At the same time a diverse, if equally scientifically focused, opposition to addiction neuroscience is emerging. In this struggle over the merits of addiction neuroscience are elements of a uniquely 21st-century public engagement with science. No longer trusted by the public as the unerring source of objective knowledge about the world, science is, at least in some contexts, increasingly treated as just one voice among many. Observing the difficulties this loss of faith in science poses for effective action on pressing issues such as climate change, philosopher Bruno Latour develops a different (ecological) approach to scientific knowledge, one that for the first time allows scientists (and other “moderns”) to understand it for what it really is and locate it “diplomatically” alongside other modes of knowing. In this article, I ask whether a similar innovation is needed to allow more effective understanding of addiction. I explore this question by analyzing two recent, widely discussed, popular books (Marc Lewis’s Memoirs of an Addicted Brain: A Neuroscientist Examines His Former Life on Drugs, 2011 and Carl Hart’s High Price: A Neuroscientist’s Journey of Self-discovery that Challenges Everything You Think You Know About Drugs and Society, 2013) as well as reviews of these books. Written by neuroscientists, and drawing heavily on personal memoir to illustrate and ratify their competing views on drugs and addiction, both books crystallize contemporary dilemmas about science, empiricism, and the nature of evidence and truth. How are we to understand their mix of “scientific fact” and individual self-observation, what does this mix suggest about scientific knowledge, and what are its implications for dominant notions of “evidence-based” drug policy and treatment? I argue that these books both trouble and reinforce our taken-for-granted distinctions between science and personal stories, between objectivity and subjectivity, and note the lost opportunities the books represent for a more searching and productive (Latour might say “ecological”) engagement with science.